‘Our Only Heaven’: Nature Veneration, Quest Religion, and Pro-Environment Behavior - Zaleha, Bernard Daley (Journal for the Study of Religion, Nature and Culture, 2013)
Utilizing the Pure Pantheism/Dualistic Theism/Nihilistic Atheism sacrality scale as a heuristic, I survey sociological/social psychological studies assessing whether people’s values and religious worldviews affect the likelihood of pro-environment behavior. One set of studies divides environmental values into three types: (1) self-interest (or egoistic) values; (2) humanistic altruism, and (3) biospheric altruism. Another study analyzes three types of self-construal as pro-environment indicators: (1) independent, (2) interdependent, and (3) metapersonal. Analyzing these models in light of the tripartite social psychological model of (1) religion as means; (2) religion as an end unto itself; and (3) religion as quest, I demonstrate that both the biospheric and metapersonal orientations, and perceptions that tend toward the pantheistic end of the sacrality scale, are the strongest predictors of pro-environment behavior. Put simply, nature veneration is predictive of pro-environmental behavior. I further argue that available data make the testing of this hypothesis worth pursuing whether naturevenerating religions are growing in the United States and beyond.